Service Export Sophistication and Economic Growth - Mishra, Saurabh; Lundstrom, Susanna; Anand, Rahul (2012)
Can increasing sophistication in service exports lead to economic growth? Although services were historically produced primarily for domestic consumption, they are gradually becoming more productive, tradable and unbundled. The authors construct an index of "service exports sophistication" to document this phenomenon. Panel data estimations indicate a positive association between growth in per capita income and higher sophistication of service exports. The results also suggest that this phenomenon is growing in importance over time. Considering the limits of traditional industrialization in igniting global growth, the results provide an alternative channel.